The Relation Between Home and Identity in The Girl From The Golden Horn by Kurban Said - Paramita Ayuningtyas (Bina Nusantara University, 2012)
The focus of this research entitled The Relation between Home and Identity in The Girl from The Golden Horn by Kurban Said is the relation of meaning of home and someone’s perspective of identity. The research is conducted by analyzing the two main characters, Asiadeh and Abdul Kerim, and relating the conflicts they are facing to identity concept by Stuart Hall. Hall mentioned that identity is a process of becoming and also a matter of someone’s position in the world. The discussion points out the identity crisis experienced by Asiadeh and Abdul Kerim when as Easterners, they have to live in Western world. It also shows that the characters finally succeeded in finding their home when they have taken their duty given by their their identity as the part of Ottoman Empire, which is to marry each other.